The Role of Gender Identity in Framing a Feminine Understanding of the Hijab by Female Students: A Sociological Reading of the Algerian University Scene - Guenifa, Nora; Mokrani, Anouar; Tali, Jamal (Al-Adab Journal, 2025)
The hijab has always been associated with religious meenings and social customs. This is so because it formalizes the feminine appearance in the public sphere as a male dominated environment, and grants the female body purity, chastity and modesty, while at the same time obligating women to adhere to a moral behavioral pattern that arranges their relationship with the male space to the extent that the hijab reflects male authority and virility in conservative societies. Nevertheless, its dominance over women is declining due to the complexity and demands of daily life. Women’s interpretations of their general context (study, work, shopping...) and the style of dress that it entails grants them with symbolic resources that provide space for negotiation as well as confrontation all at the same time, which allows them to freely choose a dress appearance that meets their expressive needs for their gender identity. However, their confrontation with a society that strongly adheres to its customs and traditions with regard to women, has produced a feminist type that appears as submissive to patriarchal demands in terms of veiling. The contradictory treatment of women in society has produced a multiplicity of different forms of hijabs, which have made their imposing presence in the public sphere and have been systematically linked to women’s Muslim identity as a type of socialization resistant to Western culture as well as to political-religious movements. Using qualitative methods this article aims to analyze a sample of 30 semi-structured interviews, on the social and cultural influences that construct the image of women who define their independent gender identity in rational relationships within the constraints of their social context. The relationship of these women with the hijab provides the reader with interesting and ambiguous findings that contradict all expectations; their religious knowledge is mainly absent from their donning of the hijab and its religious purposes, which empties it of its ideological load, and thus engages in a wave of normalization with the transformation imposed by the social market to become a commodity that rearranges the hijab as a versatile and complex consumer value for women who are diverse in their composition as a complex social group.